The Essential Structure of Self-reported Needs of Adolescents with ADHD: A phenomenological study - Áslaug Birna Ólafsdóttir (2007)
This study was undertaken in 2006–2007, as part of a master’s programme in nursing at the Royal College of Nursing Institute of Higher Education in London, in collaboration with the University of Akureyri. The aim was to increase understanding of the lived experiences of adolescents with ADHD with emphasis on their self-reported needs – from their own perspective. This study is a phenomenological one within the Vancouver School which is an interpretive-constructivist school of doing phenomenology. The sample consisted of ten adolescents aged from 11 to 16 years old in 2006, with ADHD, who were living in Iceland. I met eight of the young people once and two of them twice, resulting in a total of 12 dialogues. The essential structure of the phenomenon was constructed firstly by understanding the individual cases and then by understanding them as a whole. The young people’s accounts revealed a multifaceted reality: firstly, their need for intimacy and closeness; secondly, their need for knowledge and understanding – not prejudice; thirdly, their need to be supported, at home, at school and by peers and pets; and finally, their need for a positive self-image with self-knowledge and knowledge about ADHD, for the identification of strengths and building on them, and for optimism, faith and hope. The overriding theme describing the needs of the young people was constructed as the need to be accepted as you are. This and other studies show that it can be difficult to be a young person with ADHD, not least in elementary school. The problems that young people with ADHD experience at school have a huge impact on their lives, often in the most detrimental sense, resulting in negative self-perception and unhappiness. However, the young people also exhibit many great strengths, interests and talents, and it is extremely important for their health and well-being that they should build on these in order to experience positive feelings and develop a strong self-image. Furthermore, they can be supported effectively by parents, ...